Development of hybrid polypropylene composites reinforced with chemically modified rice straw and foxtail millet husk for EV automotive applications - Megha Tirumala Sai Tangellamudi; G. Prasanthi; Shankar Char M. Sutar (Scientific Reports, 2026)
Abstract In this study, lightweight hybrid composites based on polypropylene (PP) reinforced with agricultural residues rice straw (RS) and foxtail millet husk (FMH) were developed for potential automotive applications in electric vehicles. A fiber mixture consisting of RS and FMH in a 1:1 ratio was subjected to chemical treatments using alkaline sodium hydroxide (NaOH) and tannic acid to extract cellulosic fibers and to compare the effectiveness of these treatments in improving fiber matrix interfacial adhesion. Hybrid composites containing 5–15 wt% fibers were fabricated via co-rotating twin-screw extrusion followed by compression moulding. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the removal of hemicellulose, lignin, and waxy components after alkali treatment, while tannic acid treatment introduced phenolic functional groups on the fiber surface. Scanning Electron Microscopy (SEM) revealed enhanced surface roughness, fibrillation, and improved dispersion of treated fibers within the PP matrix. Mechanical testing demonstrated significant improvement in tensile strength (29.51 MPa), flexural strength (64.61 MPa), and impact strength (6.976 kJ/m²) compared to untreated composites. These values exceed those typically reported for conventional natural fiber-reinforced PP composites tensile 20 to 28 MPa, flexural 35 to 60 MPa, indicating enhanced mechanical performance. The melt flow index (MFI) decreased to 3.649 g/10 min with increasing fiber loading, indicating improved melt resistance while maintaining adequate processability. The improved properties are attributed to the synergistic effect of hybrid fibre reinforcement and enhanced interfacial bonding facilitated by chemical treatments. These findings demonstrate that PP-based RS–FMH hybrid composites can serve as sustainable and lightweight materials for EV automotive components.